Employee Retirement: A Review and Recommendations for Future Investigation - Wang, Mo; Shultz, Kenneth S. (Journal of Management, 2010)
Despite the obvious importance of retirement to employees, their employing organizations, and the larger society, the last comprehensive review of employee retirement in the field of organizational science was published more than 20 years ago. As such, the first purpose of this review is to provide a summary of key theoretical and empirical developments in employee retirement research since Beehr in 1986. A second purpose of this review is to highlight inconsistent findings revealed by studies that were designed to answer the same research questions. By identifying and scrutinizing those inconsistent findings, this study expects to provide suggestions and recommendations to further the theoretical development in the field of retirement research to address these research gaps. As a result, this proposed review would be of interest to scholars in a wide variety of areas within the organizational sciences, including human resource management, organizational behavior, organizational theory, and research methods.